(3GdMGhj GdcHjQ aj GdaQhYs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s
(3ChdgG (B:s
(3jHJOC HaUd (B( (3hGdGYJQGV GdKGfi Cf bGdhG de bGd GNJUQJ bHd GNJUGQg hgPG cPH (B) s
(3BNQgG (B:s
(3jfJgi HaUd (B( (3aCeG GdeHJdi HGdPi aYdi VQjHjf (B) s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B628s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdabg GdTGaYjs